Comparison of Staphylococcus aureus strains for ability to cause infective endocarditis and lethal sepsis in rabbits - Spaulding, Adam R.; Satterwhite, Erin A.; Lin, Ying-Chi; Chuang-Smith, Olivia N.; Frank, Kristi L.; Merriman, Joseph A.; Schaefers, Matthew M.; Yarwood, Jeremy M.; Peterson, Marnie L.; Schlievert, Patrick M. (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus is a major cause of infective endocarditis (IE) and sepsis. In addition, 50% of IE survivors develop strokes and metastatic abscesses due to the release of emboli from infected valves. Both methicillin-resistant (MRSA) and methicillin-sensitive (MSSA) strains cause IE and sepsis, and they may be categorized by pulsed-field gel electrophoresis, for example clonal types USA200, 300, and 400. We hypothesize that secreted virulence factors contribute to their differential ability to cause IE and/or sepsis. Rabbits are an excellent model for studying IE, which over the course of 4 days are monitored for development of vegetations (the hallmark signs of IE), and sepsis, as S. aureus are administered intravenously. Rabbit cardiac physiology is similar to humans, and rabbits exhibit susceptibility to superantigens and cytolysins produced by these clonal types of S. aureus. We examined the differential ability of community-associated MRSA and MSSA strains (5 USA200 or related strain FRI1169, 3 USA300, and 2 USA400) to cause vegetations versus lethal sepsis in rabbits. USA200 and related strain FRI1169 exhibited intermediate LD50s in sepsis (5x106-5x108) colony-forming units (CFUs), and 4/5 caused significant IE. In contrast, USA300 strains were highly effective in causing lethal sepsis (LD50s of 1 x 106-5 x 107 CFUs) but were minimally capable of causing IE. USA300 variant strain Newman was not highly lethal (LD50 of 2 x 109 CFUs) but was highly effective in causing IE. USA400 strains were both highly lethal (LD50s of 1 x 107-5 x 107 CFUs) and highly effective causes of IE. Additional studies showed that phenol soluble modulins produced by FRI1169 were important for sepsis but did not contribute to IE. Our studies show that these clonal groups of S. aureus have differential abilities to cause IE and lethal sepsis and suggest that secreted virulence factors, including superantigens and cytolysins, account for these differences.